To solve the equation $\frac{5}{3}x + \frac{11}{3} = -\frac{4}{3}$, we can first subtract $\frac{11}{3}$ from both sides of the equation:
$\frac{5}{3}x + \frac{11}{3} - \frac{11}{3} = -\frac{4}{3} - \frac{11}{3}$.
This simplifies to:
$\frac{5}{3}x = -\frac{15}{3}$.
Next, we can simplify the right side of the equation:
$\frac{5}{3}x = -5$.
Now, we want to isolate $x$, so we can multiply both sides of the equation by $\frac{3}{5}$:
$\frac{3}{5} \cdot \frac{5}{3}x = -5 \cdot \frac{3}{5}$.
This gives us:
$x = -3$.
Therefore, the solution to the equation $\frac{5}{3}x + \frac{11}{3} = -\frac{4}{3}$ is $x = -3$.
The equation 5/3x + 11/3 =−4/3 is solved as follows. Fill in the correct numbers to complete the solution
1 answer